The Morphometric Character and Mitochondrial 16S rRNA Sequence of Portunus pelagicus - Fujaya, Yushinta; Hidayani, Andi Aliah; Asphama, Andi Ivo; Trijuno, Dody Dharmawan; Tenriulo, Andi; Parenrengi, Andi (Aquacultura Indonesiana, 2015)
Blue swimming crab (Portunus pelagicus) colors have variations from different habitats and they have different vitality. The purpose of this study was to analyze the diversity of the P. pelagicus using morphometric and 16SrRNA mitochondrial sequence.  There were three groups of blue swimming crab characterized by differences in color and density patterns of spots.  The result of Canonical discriminant analysis showed that there were morphometric differences among the three groups.  The main distinguishing morphometric characteristics are the ratio of carapace width and length as well as the ratio of the length and width of cheliped merus.  The third group of crab is also has similarity about 98-99% by the Portunus pelagicus 16S rRNA sequences available in gene banks.  These studies had concluded that differences in color and pattern of the spot density have also morphometric and genetic differences. At least there were two groups based on genetic variation of Portunus pelagicus from Barru Regency waters which may have a variety of different properties.  Further research is needed to study the adaptation abilities of the two groups of crab on the condition of aquaculture as a potential domestic animal.Keywords: Crab; Portunus pelagicus; Morphometric; 16S rRNA.